Attitude toward female genital mutilation among Somali and Harari people, Eastern Ethiopia - Abathun AD; Sundby J; Gele AA (Dove Medical Press, 2016)
Asresash Demissie Abathun,1 Johanne Sundby,2 Abdi A Gele3 1Faculty of Medicine, Institute of Health and Society, 2Department of Community Medicine and Global Health, Institute of Health and Society, University of Oslo, 3Department of Nursing and Health Promotion, Oslo and Akershus University College, Oslo, Norway Background: Female genital mutilation (FGM) is a worldwide problem, and it is practiced by many communities in Africa and Asia as well as immigrants from those areas. This practice results in short- and long-term health consequences on women’s health. Like many other developing countries, FGM is widely practiced in Ethiopia, especially among Somali and Harari ethnic groups. Despite intensive campaigns against FGM in Ethiopia, since 2011, it has been practiced in the aforementioned communities. There is no recent information as to whether these campaigns have an impact on the attitude and practice of the community regarding FGM. This qualitative research was aimed at exploring the attitudes of Somali and Harari people between 18 and 65 years toward FGM.Methods: A purposive sampling technique was used to recruit 64 (32 in each region) participants. Data were collected from October to December 2015 in Somali and Harari Regions.Results: The findings showed that there was a strong support for the continuation of the practice among female discussants in Somali region, whereas male discussants from the same region and the majority of the participants from Harari region had a positive attitude toward the discontinuation of the practice. Marriageability was the major reason for practicing FGM in Somali region, whereas making girls calm, sexually inactive, and faithful for their husbands were mentioned in Harari region. Although young men in both the regions prefer to marry uncircumcised girls, the study showed that there are some differences in the attitude toward the FGM practice between the people in the two regions.Conclusion: The findings show that there is an attitudinal difference between the people in the two regions, which calls for behavioral change communication using women-centered approach and culturally appropriate strategies. As young people in both the regions had the intention to marry uncircumcised girls, there has to be a strong advocacy and multisectoral collaboration to stop FGM in both the regions. Keywords: female genital mutilation, attitude, abandonment, health effect, reason